Market expansion may harm the supplier in a bilateral monopoly - Noriaki Matsushima; Laixun Zhao (Osaka University, Institute of Social and Economic Research (ISER), 2018)
We consider a bilateral monopoly with a supplier and a buyer. Their trading terms are determined through negotiations, but affected by the buyer's efforts to search for outside suppliers. We find surprisingly that a market expansion may harm the supplier.
Keywords: L14; L22; 330; Bilateral monopoly; Nash bargaining; outside suppliers